Downregulation of proinflammatory cytokines in HTLV-1-infected T cells by Resveratrol. Issue 1 (December 2016) - Fuggetta, Maria; Bordignon, Valentina; Cottarelli, Andrea; Macchi, Beatrice; Frezza, Caterina; Cordiali-Fei, Paola; Ensoli, Fabrizio; Ciafrè, Stefania; Marino-Merlo, Francesca; Mastino, Antonio; Ravagnan, Giampietro
Abstract Background Human T-cell leukemia virus (HTLV-1) is a lymphotropic retrovirus associated to adult T cell leukemia (ATL) and to non-neoplastic inflammatory conditions affecting the central nervous system, lung or skin. The inflammatory disorders associated to HTLV-1 are mediated by different proinflammatory cytokines as IL-1α, IL-6, TNF-α. The release and the role of IL-17 is still debated. Aims of this study were to analyze IL-17 induction by HTLV-1 infection and to determine whether resveratrol (RES) is able to down regulate the pathway of cytokines production either in HTLV-1 chronically infected MT-2 cell line or in human CD4+ cells infected in vitro with HTLV-1. Methods MT-2 and HTLV-1 infected CD4+ cells were analyzed for proinflammatory cytokine production before or after RES treatment. The concentrations of IL-17, IL-1α, IL-6, and TNF-α were measured in cell culture supernatants by ELISA and SearchLight™ technology. The IL-17 mRNA expression was evaluated by RT-PCR. NF-kB activation was detected by non-radioactive, Electro Mobility Shift Assay (EMSA). HTLV-1 RNA expression was detected by Real-time-PCR (RQ-PCR). Results We found that RES is capable of inducing a dose-dependent inhibition of IL-1α, IL-6 and TNF-α production in vitro and can down regulate the expression of IL-17 at both mRNA and protein levels in HTLV-1 infected cells. This effect was associated with a dose-dependent inhibition of the of the nuclear factor kappa-B (NF-kB) activity. Conversely, RES did not apparently affect HTLV-1 proliferation. Conclusions These results support the anti-inflammatory properties of RES, suggesting that it might be a useful therapeutic agent for the treatment of HTLV-1 related inflammatory diseases.